Attitudes of nursing home residents towards staying in a nursing home: a qualitative study - Maryam Salem Khalaf Al-Anazi, Eman Sanad Alanazi, Fawzah Sabih H Alkhaldi , Hind Sabih H Alkhaldi, Mesfer Khalaf Alrashidi, Abeer Hassn Aldfeeri (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
This study aims to investigate the attitudes of elderly residents in nursing homes towards their stay and to distinguish between various types of these attitudes. Context: The demand for nursing care among older individuals is on the rise, leading to the establishment of nursing homes in major cities despite the prevalent cultural norm of family care. Methodology: Semi-structured interviews based on guidelines were conducted with 21 residents across four different nursing homes . Qualitative content analysis was applied to analyze the interview data. Findings: The study identified two main categories of residents: those who were placed in the nursing home by close relatives and those who made the decision to move independently. Factors such as social networks and individual self-help capabilities played a significant role in shaping residents’ decision-making processes. Conclusion: Nursing homes in Egypt serve diverse functions depending on the needs and circumstances of older individuals. While charitable institutions may serve as a last resort for those with limited income and social support, nursing homes can offer social interaction opportunities and medical care for more financially stable residents.